The Integration of Science and Religion in the Fiqh Subject at Darul Mursyid Private Islamic Junior High School - Siregar, Hendra Irwandi; Hasibuan, Zainal Efendi (Borneo Journal of Islamic Education, 2025)
This study aims to explore and analyze how the integration of science and religion can be implemented in the Fiqh subject at Darul Mursyid Private Islamic Junior High School (MTs Swasta Darul Mursyid). Based on the premise that education is a vital foundation for shaping students' character and understanding, this research focuses on teaching methods that combine scientific aspects with religious values. The method used in this study is a qualitative approach, with data collected through interviews, observations, and document analysis. The respondents consist of Fiqh teachers and students at MTs Swasta Darul Mursyid. The findings reveal that the integration of science and religion in Fiqh learning not only enhances students’ understanding of the subject matter but also fosters critical and creative attitudes in practicing religious teachings. The conclusion of this study emphasizes that the application of such integration is crucial in addressing the increasingly complex challenges of the times and in strengthening character education based on Islamic values. The study recommends that educators continue to develop innovative and interactive teaching methods so that students can better understand and apply scientific knowledge within the context of religious teachings.